(untitled) (Bangladesh Rice Journal, 2026)
Genotype × environment (G × E) interaction is a critical consideration in rice breeding, as it determines the adaptability and stability of genotypes across diverse agroecological zones. This study aimed to explore the most suitable and stable Boro rice genotypes for Bangladesh. In this study, seven rice genotypes were evaluated in Boro season across twelve locations in Bangladesh during the 2024 Boro season to investigate genotype-environment interaction (GEI) and yield stability performance. The experiment utilized three replications of a completely randomized block design. The analyses were performed through the Additive Main Effects and Multiplicative Interaction (AMMI) and Genotype plus Genotype × Environment (GGE) biplot models. The AMMI analysis revealed that environment accounted for the largest proportion of total variation (51.9%), followed by G × E interaction (16.7%) and genotype (3.7%) The AMMI identified genotypes G2 and G6 as stable, high-yielding genotypes. The GGE biplot analysis accounted for 78.4% of the total G × E interaction, with identifying G2 and G6 as elite genotypes for broad adaptation with high yield potential. Both the AMMI and GGE analyses consistently identified genotypes G2 and G6 as stable and emerge as elite genotypes for broad adaptation with high yield potential, while G1 and G5 show strong performance in specific environmental sets. The combined use of AMMI and GGE analyses effectively captured both yield stability and adaptability patterns, supporting that G2 was broadly adapted, high-yielding entries suitable for rice development program in Bangladesh. Bangladesh Rice J.28(1): 69-79, 2024